This is Tom = /zyzys'tom/. Pronunciation in Beginners' EFL Textbooks Then and Now - Sobkowiak, Włodzimierz (Research in Language, 2012)
The textbook appears to be one of the most fundamental elements of all formal-setting foreign language teaching and learning. Textbooks function in a foreign language classroom in many capacities (Cunningsworth 1995), one of which is the provision of text, used as a model for language practice, including practice of pronunciation. The changing methodological trends in EFL pedagogy over the decades affect EFL textbook pronunciation treatment in a variety of ways. In this paper a simple feasibility study is presented whereby a few beginners’ textbooks are compared with respect to their handling of pronunciation in the first unit of the course. Four textbooks come from about ½ century ago, and three are sampled from among those currently available. On the descriptive level, some analysis is offered of the phonetic (and especially phonolapsological) characteristics of the sampled texts, as they changed through time. On the level of application, it is claimed that, while the lexico-grammatical and pedagogical limitations on the content of the first lessons/units in EFL textbooks leave authors little space for phonetic control, a modicum of such control is feasible if attention is paid to such variables as pronunciation difficulty and L1 transfer. The Phonetic Difficulty Index (PDI), which is briefly introduced in the paper, can be used to measure and control some of these variables and give the textbook authors and users a useful teaching/learning instrument.